MEDIASI BUDAYA LOKAL BERPRESPEKTIF GLOBAL DALAM PEMBELAJARAN BAHASA ASING - Mohamad Syaefudin (Adabiyyāt: Jurnal Bahasa dan Sastra, 2013)
The importance of expressing local geniuses in other language could be the best way to learn a foreign language. Learning strategies which mediates the local geniuses and foreign values expressed in a foreign language brings a global perspective of the foreign culture. The cultural connection will be achieved not only from the messages brought by the local geniuses but also the cultural values of the foreign language. Eventually learners realize that by recognizing their own culture, recognizing and appreciating other culture will not be difficult. The French and the Javanese culture get along well in this research.